A non-contact capacitance type level transducer for liquid characterization - Khan, Sheroz; Htike, Kyaw Kyaw; Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khalifa, Othman Omran; Khan, Saman S. (2008)
The liquid properties such as buoyancy, pressure at a depth, relative electrical permittivity, electrical conductivity, thermal conductivity, absorption of radiation, liquid surface reflection of sound or light waves, are used to design the different types of liquid level transducers for liquid level measurement in any process industry. The contact-type level-sensing transducers have the disadvantage that their characteristic properties may change due to physical or chemical reaction between the liquid and the probing material, and hence may affect accuracy besides their life time. The non-contact-type level-sensing probes may have longer life period, but they are comparatively costly and require various environmental and experimental precautionary measures when being used. In this paper, a low-cost non-contact capacitance type liquid level measuring technique has been designed and used for liquid identification objectives. The results obtained are very much consistent with the theoretical derivations.